Anxiety and the patient with breast cancer: A review of current research and practice - H.M. Van Oers; L. Schlebusch (South African Family Practice)
Breast cancer is one of the most common cancers worldwide. Statistics reveal that the number of women diagnosed with breast cancer is increasing in South Africa. In particular, there appears to be a growing incidence in younger, black women in urban areas. Family practitioners and oncology healthcare professionals are going to be treating an increasing population of patients with breast cancer. Research has shown that in many instances, the psychological needs of patients with breast cancer are not adequately addressed, and that often the physical crisis is seen as more immediate. Also, healthcare professionals and oncologists may not be aware of the prevalence of co-morbid psychological distress, and thus do not focus on this aspect of the diagnosis. As a result, women who experience psychological distress during and after treatment may not be referred for psychological management. This may have a significant impact on their quality of life during this period and may even affect their compliance with treatment. This ultimately has implications for their ongoing health and survival. This review of the available literature aims to heighten awareness of healthcare professionals to the current situation, with a view of improving the mental health care of South African patients with breast cancer.